Transvaginal ultrasound training for the obstetrics and gynecology resident: A multisite randomized controlled trial of educational DVD. Issue 2 (7th December 2018) - McCurdy, Rebekah J.; High, Brooke; Schnatz, Peter F.; Baxter, Jason; Jiang, Xuezhi
Abstract: Purpose: Residents in obstetrics and gynecology are deemed to be proficient in transvaginal ultrasound (TVUS) upon graduation, although TVUS education in residency is not standardized. The objective of this study is to assess for improvement in TVUS knowledge among residents after viewing an educational DVD. Methods: This is a multisite prospective randomized controlled trial using an educational DVD ("Gynecology: Beginners Only"), compared to routine education. All participants completed a pretest on TVUS images and principles. The intervention group repeated the test after DVD viewing. During the trial, performing and logging TVUS examinations were encouraged. All enrolled residents repeated the test 6–10 months later. Results: Fifty‐seven residents completed the study with a mean pretest score of 9.7 (1st year resident 9.8, 2nd year resident 9.6, 3rd year resident 10.1, 4th year resident 9.4, P  = .763), with a mean of 31.5 TVUS examinations logged prior to intervention. The mean score in the intervention group ( n  = 34) improved significantly after viewing (11.2, P  < 0.003). This improvement did not persist 6‐10 months later on a follow‐up quiz (mean 10.7, P  = .894). At completion of the study, participants logged an average of 56.7 TVUS examinations. Conclusion: An educational DVD is easily implemented and demonstrates short‐term benefit. Exploration of different teaching modalities in development of a comprehensive training program may improve long‐term retention.